Use of Autoantigen-Loaded Phosphatidylserine-Liposomes to Arrest Autoimmunity in Type 1 Diabetes - Pujol-Autonell, Irma (PLoS One, 2015)
INTRODUCTION: The development of new therapies to induce self-tolerance has been an important medical health challenge in type 1 diabetes. An ideal immunotherapy should inhibit the autoimmune attack, avoid systemic side effects and allow β-cell regeneration. Based on the immunomodulatory effects of apoptosis, we hypothesized that apoptotic mimicry can help to restore tolerance lost in autoimmune diabetes. OBJECTIVE: To generate a synthetic antigen-specific immunotherapy based on apoptosis features to specifically reestablish tolerance to β-cells in type 1 diabetes. METHODS: A central event on the surface of apoptotic cells is the exposure of phosphatidylserine, which provides the main signal for efferocytosis. Therefore, phosphatidylserine-liposomes loaded with insulin peptides were generated to simulate apoptotic cells recognition by antigen presenting cells. The effect of antigen-specific phosphatidylserine-liposomes in the reestablishment of peripheral tolerance was assessed in NOD mice, the spontaneous model of autoimmune diabetes. MHC class II-peptide tetramers were used to analyze the T cell specific response after treatment with phosphatidylserine-liposomes loaded with peptides. RESULTS: We have shown that phosphatidylserine-liposomes loaded with insulin peptides induce tolerogenic dendritic cells and impair autoreactive T cell proliferation. When administered to NOD mice, liposome signal was detected in the pancreas and draining lymph nodes. This immunotherapy arrests the autoimmune aggression, reduces the severity of insulitis and prevents type 1 diabetes by apoptotic mimicry. MHC class II tetramer analysis showed that peptide-loaded phosphatidylserine-liposomes expand antigen-specific CD4(+) T cells in vivo. The administration of phosphatidylserine-free liposomes emphasizes the importance of phosphatidylserine in the modulation of antigen-specific CD4(+) T cell expansion. CONCLUSIONS: We conclude that this innovative immunotherapy based on the use of liposomes constitutes a promising strategy for autoimmune diseases.